2004
DOI: 10.1073/pnas.0402775101
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sulfur and iron on dissolved arsenic concentrations in the shallow subsurface under changing redox conditions

Abstract: The chemical speciation of arsenic in sediments and porewaters of aquifers is the critical factor that determines whether dissolved arsenic accumulates to potentially toxic levels. Sequestration of arsenic in solid phases, which may occur by adsorption or precipitation processes, controls dissolved concentrations. We present synchrotron x-ray absorption spectra of arsenic in shallow aquifer sediments that indicate the local structure of realgar (AsS) as the primary arsenic-bearing phase in sulfate-reducing con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
311
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(332 citation statements)
references
References 43 publications
19
311
1
1
Order By: Relevance
“…Microbial sulfate reduction often resulted in subsequent precipitation of As by a mixed population of SRB (Jong and Parry 2003;Rittle et al 1995). Conversely, under sulfate-reducing conditions, As may react with excess sulfide to first form soluble thioarsenite complexes, which may then precipitate as As-S solid phases such as amorphous As 2 S 3 or realgar (AsS) as dissolved sulfide concentrations increase (O'Day et al 2004;Bostick et al 2005). The thioarsenite complexes are more easily formed in a low Fe 2+ and high organic matter environment (Couture et al 2013;Burton et al 2014), while not commonly reported in paddy soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial sulfate reduction often resulted in subsequent precipitation of As by a mixed population of SRB (Jong and Parry 2003;Rittle et al 1995). Conversely, under sulfate-reducing conditions, As may react with excess sulfide to first form soluble thioarsenite complexes, which may then precipitate as As-S solid phases such as amorphous As 2 S 3 or realgar (AsS) as dissolved sulfide concentrations increase (O'Day et al 2004;Bostick et al 2005). The thioarsenite complexes are more easily formed in a low Fe 2+ and high organic matter environment (Couture et al 2013;Burton et al 2014), while not commonly reported in paddy soil.…”
Section: Discussionmentioning
confidence: 99%
“…5), which may be through the coprecipitation of As(III) with reducing S 2− and iron sulfides under anaerobic conditions. It has been suggested that low As mobility in soil solution is related to the conditions of high sulfur in anaerobic paddy soils and also in sediments of aquifers, peat, and floodplains (O'Day et al 2004;Langner et al 2012;Burton et al 2014). The release of As to soil solution and its accumulation in rice plants in the transition from oxidizing to reducing may depend on the amount of available iron and sulfur in the paddy soil, rate of reductive dissolution of Fe(III) phases, SO 4 2− reducing rate, and the rate of As precipitation with S 2− .…”
Section: Discussionmentioning
confidence: 99%
“…In geothermal environments, mobility of As can be partly controlled by its chemical speciation. The dominant As species in a given environmental setting is controlled by many parameters, such as pH, temperature, adsorption and dissolution reactions and redox conditions which are driven by the presence of organic matter and inorganic electron donors such as sulfides [8][9][10][11][12][13]. Arsenic is generally released from the host rock by dissolution under reducing conditions, where high residence time, and high temperature and pressure of the fluids favor its mobilization [2,14].…”
Section: Introductionmentioning
confidence: 99%
“…Arsenic is a toxic trace element that is ubiquitous in nature, and is usually concentrated in mineral sulfide ore bodies (Fleet et al, 1989;Huston et al, 1995;Smedley and Kinniburgh, 2002). Serious health problems like arsenicosis, keratosis and certain types of cancers (e.g., skin, lungs, liver, bladder and kidneys) have been linked to the chronic intake of this element through contaminated drinking water sources (Cebrian et al, 1983;Chakraborty and Saha, 1987;Chen et al, 1985;Chen et al, 1992;O'Day et al, 2004;Sengupta, 2002;Smith et al, 1992;Tseng et al, 1968;Zaldivar, 1974).…”
Section: Introductionmentioning
confidence: 99%